2016
DOI: 10.20882/adicciones.745
|View full text |Cite
|
Sign up to set email alerts
|

El uso problemático de videojuegos está relacionado con problemas emocionales en adolescentes

Abstract: Problem use of video games is an increasing risk behaviour. High exposure of adolescents to video games has been linked to a variety of disorders, but the relationship between problem video game playing and emotional welfare is unknown. The aim of the study is to analyse problem video game playing in a sample of adolescents and to determine whether there are differences between online and offline players, in addition to examining its relationship with anxiety and depressive symptomatology. A sample of adolesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
10
0
22

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 23 publications
4
10
0
22
Order By: Relevance
“…Although there are benefits of electronics for children, potential negative associations with childhood mental health are an emerging topic of interest in current research. There is some evidence that greater child anxiety is associated with higher overall levels of general electronic media use [36], as well as with greater use of specific types of electronics, such as video games [5, 7–9], and social media [9–12]. However, prior research has not examined whether such associations with anxiety remain significant after controlling for depression, which is often comorbid with anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are benefits of electronics for children, potential negative associations with childhood mental health are an emerging topic of interest in current research. There is some evidence that greater child anxiety is associated with higher overall levels of general electronic media use [36], as well as with greater use of specific types of electronics, such as video games [5, 7–9], and social media [9–12]. However, prior research has not examined whether such associations with anxiety remain significant after controlling for depression, which is often comorbid with anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has identified media exposures, such as video games, television, movies, and the Internet, to be associated with the development of depression among adolescents (Bickham et al, 2015; Gonzálvez et al, 2016; Holfeld and Sukhawathanakul, 2017; Liu et al, 2016; Primack et al, 2009). Other research has extended this by suggesting that use of social media is associated with depressive symptoms and a decline in well-being among both adolescents (Pantic et al, 2012) and adults (Kross et al, 2013; Lin et al, 2016; McDougall et al, 2016; Shensa et al, 2016).…”
mentioning
confidence: 99%
“…Pero la investigación sobre estas frecuencias elevadas de utilización no solo se ha centrado en Internet, sino también en diversas tecnologías que van desde las Tecnologías de la Información y Comunicación en general (García-Oliva et al, 2017;Gairín y Mercader, 2018) hasta los juegos por Internet (Bertrán y Chamarro, 2016;Martín et al, 2017), videojuegos (Gonzálvez et al, 2015;Espejo et al, 2018), teléfonos móviles (Pedrero et al, 2012;Gaspar y Cuesta, 2015) y, por supuesto, las RSO.…”
Section: Redes Sociales Online Y Adicciónunclassified